The Effect of Nitrogen Fertilization on the Growth of Citrus and its Infection Rate with Tetranychus Urticae Koch - Sakr, Ibrahim Aziz; Ismail, Haisam Muhamad; Jadeed, Maison Ahmad (Latakia University Journal -Biological Sciences Series, 2013)
The experiments aimed to study the effect of nitrogen fertilization amount and its application times on the growth of citrus seedlings of Aafawi and Navelcultivar, and on its infection rate with Tetranychus urticae Koch. The experiments were carried out in the Faculty of Agriculture/Tishreen University.Three levels of urea were used(A = 0.5,B = 1, C = 1.5g/seedling). These amounts were addedin different quantities and at different times.In experiment N1,the full amount was added on1stof March;in experiment N2 the amount was divided equally and was addedon1stof March and 1stof April; andit was divided into three amounts in the third experiment N3 on 1st of March, 1st of April and 1st of May. Results showed that transaction (C) achieved the greatest growth of seedlings comparedto the control against the greatest injury when urea was added altogether(the average number of mites183.5).The transaction achieved low injury when urea was added at three times (135 mites) in the case of cultivar Navel, and (132) against (122) in the case ofcultivar Alaafawi.It was also found that the growth rate was stable (from March to September) in experiment N3(additionatthree times) comparedtoexperiment N1 (one addition).Adding nitrogen fertilizerat many times achieves stable growth to citrus seedlings, and lowerstheinfection ratewith Tetranychus urticae Koch.